1987
DOI: 10.1080/00288330.1987.9516206
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chlorine and chlorine dioxide on pathogenic free‐living amoebae (PFLA) in simulated natural conditions: The presence of bacteria and organic matter

Abstract: Bacteria and bovine faecal matter were introduced into cultures of pathogenic free-living amoebae, with chlorine or chlorine dioxide. The bacteria and faeces were to simulate natural conditions for a more exacting test of disinfectant demand when compared to axenic conditions. Both chlorine and chlorine dioxide were effective disinfectants under all conditions tested. Axenically and monoxenically cultured amoebae were used, the latter exerted a greater disinfectant demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Only one experiment was conducted at each free-chlorine level, and the authors note the assertion that N. gruberi is more resistant to chlorine than N. fowleri should be interpreted in light of other studies (which generally support greater susceptibility of N. fowleri to chlorine and other disinfectants). Dawson and Brown (1987) noted greater sensitivity of N. fowleri to both chlorine and chlorine dioxide than other Naegleria spp. Dawson and Brown (1987) noted greater sensitivity of N. fowleri to both chlorine and chlorine dioxide than other Naegleria spp.…”
Section: N Fowleri Management In Drinking Water Production and Distrmentioning
confidence: 85%
See 1 more Smart Citation
“…Only one experiment was conducted at each free-chlorine level, and the authors note the assertion that N. gruberi is more resistant to chlorine than N. fowleri should be interpreted in light of other studies (which generally support greater susceptibility of N. fowleri to chlorine and other disinfectants). Dawson and Brown (1987) noted greater sensitivity of N. fowleri to both chlorine and chlorine dioxide than other Naegleria spp. Dawson and Brown (1987) noted greater sensitivity of N. fowleri to both chlorine and chlorine dioxide than other Naegleria spp.…”
Section: N Fowleri Management In Drinking Water Production and Distrmentioning
confidence: 85%
“…Similarly, Cursons et al (1980) observed that at 25°C and pH 7, N. fowleri was more sensitive to chlorine, chlorine dioxide, and ozone than N. gruberi. Dawson and Brown (1987) noted greater sensitivity of N. fowleri to both chlorine and chlorine dioxide than other Naegleria spp. for demand-free suspensions and under conditions of disinfectant demand.…”
Section: N Fowleri Management In Drinking Water Production and Distrmentioning
confidence: 85%
“…Acanthamoebae are very resistant to a range of disinfectants (5,6,8,28), and bacteria within acanthamoebae are generally afforded extra protection (16). A notable example is the opportunistic pathogen Mycobacterium avium (10), which can survive within Acanthamoeba species trophozoites and cysts (4,26), resulting in increased resistance to several antimicrobials (22).…”
mentioning
confidence: 99%
“…1114 Organic soils can also react with chlorine in chlorine-based disinfectants such that chlorine is sequestered and not freely available to act in a disinfecting capacity. 15 While protocols have been outlined for the sanitization process, less attention is devoted to the cloths used in this endeavor. 10,16 Recently, the appropriate wipe material selection has been identified as an essential tool to reduce food contamination related illnesses and deaths.…”
Section: Introductionmentioning
confidence: 99%